Antiangiogenic Cancer Therapy: Monitoring with Molecular US and a Clinically Translatable Contrast Agent (BR55)(1) - Pysz, Marybeth A. (Radiological Society of North America, Inc., 2010)
PURPOSE: To develop and test human kinase insert domain receptor (KDR)-targeted microbubbles (MBs) (MB(KDR)) for imaging KDR at the molecular level and for monitoring antiangiogenic therapy in a human colon cancer xenograft tumor model in mice. MATERIALS AND METHODS: Animal studies were approved by the Institutional Administrative Panel on Laboratory Animal Care. A heterodimeric peptide that binds to human KDR with low nanomolar affinity (K(D) = 0.5 nmol/L) was coupled onto the surface of perfluorobutane-containing lipid-shelled MBs (MB(KDR)). Binding specificity of MB(KDR) to human KDR and cross-reactivity with murine vascular endothelial growth factor (VEGF) receptor 2 (VEGFR2) were tested in cell culture under flow shear stress conditions (at 100 sec(−1)). In vivo binding specificity of MB(KDR) to VEGFR2 was tested in human LS174T colon cancer xenografts in mice with a 40-MHz ultrasonographic (US) transducer. Targeted contrast material–enhanced US imaging signal by using MB(KDR) was longitudinally measured during 6 days in tumors with (n = 6) and without (n = 6) antiangiogenic treatment (anti-VEGF antibody). Ex vivo VEGFR2 staining and microvessel density analysis were performed. Significant differences were evaluated (t, Mann-Whitney, or Wilcoxon test). RESULTS: Cell culture experiments showed four times greater binding specificity of MB(KDR) to human KDR and cross-reactivity to murine VEGFR2 (P ≤ .01). In vivo imaging signal was more than three times higher (P = .01) with MB(KDR) compared with control MBs and decreased significantly (approximately fourfold lower, P = .03) following in vivo receptor blocking with anti-VEGFR2 antibody. One day after initiation of antiangiogenic therapy, imaging signal was significantly decreased (approximately 46% lower, P = .02) in treated versus untreated tumors; it remained significantly lower (range, 46%–84% decreased; P = .038) during the following 5 days. Microvessel density was significantly reduced (P = .04) in treated (mean, 7.3 microvessels per square millimeter ± 4.7 [standard deviation]) versus untreated tumors (mean, 22.0 microvessels per square millimeter ± 9.4); VEGFR2 expression was significantly decreased (>50% lower, P = .03) in treated tumors. CONCLUSION: Human MB(KDR) allow in vivo imaging and longitudinal monitoring of VEGFR2 expression in human colon cancer xenografts. © RSNA, 2010 Supplemental material: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.10091858/-/DC1